An Empirical Test of Reder Competition and Specific Human Capital Against Standard Wage Competition - Johannes Ludsteck; Harry Haupt (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2007)
A firm that faces insufficient supply of labor can either increase the wage offer to attract more applicants, or reduce the hiring standard to enlarge the pool of potential employees, or do both. This simultaneous adjustment of wages and hiring standards has been emphasized in a classical contribution by Reder (1955) and implies that wage reactions to employment changes can be expected to be more pronounced for low wage workers than for high wage workers. We test this hypothesis (together with a related hypothesis on firm-specific human capital) by applying a bootstrap-based quantile regression approach to censored panel data from the German employment register. Our findings suggest that market clearing is achieved by a combination of wage and hiring standards adjustment.
urn:nbn:de:bvb:19-epub-1977-7
Keywords: J31; J41; C24; 330; wage setting; hiring standards; wage structure; efficiency wages; panel quantile regression; censoring; Personalbeschaffung; Qualifikation; Lohnstruktur; Arbeitsangebot; Wettbewerb; Schätzung; Deutschland